Mechanism of alcohol chemical vapor deposition growth of carbon nanotubes: Catalyst oxidation. (May 2022) - McLean, Ben; Mitchell, Izaac; Ding, Feng
Abstract: Alcohol chemical vapor deposition (ACVD) was established as one of the most promising methods for single-walled carbon nanotube (SWCNT) growth almost two decades ago however the mechanisms behind its success remain elusive. To unveil the mechanism of SWCNT growth via ACVD, we employed density functional tight binding molecular dynamics simulations, supplying ethanol to a Fe nanoparticle. Here we demonstrate the oxidation of the Fe catalyst with varying supply rates of ethanol and how the catalyst composition is controlled by the reaction pathways mediated by the hydroxyl OH radical. Following ethanol dissociation on Fe and subsequent O dissolution, the catalyst becomes oxidized and the mobility and availability of Fe to bond with C are reduced. However, SWCNT growth is promoted via the key reaction pathways of the hydroxyl H; controlling the catalyst composition through the formation and release of H2 O and H2 . These reaction pathways also demonstrate how active growth species such as ethylene can be formed preferentially to ethane from ethanol dissociation. This work provides important insight into the mechanism of how the catalyst composition changes during ACVD and can be extended to understand the catalyst nature during other O-assisted SWCNT growth processes such as H2 O-assisted supergrowth and CO/CO2 -promoted growth. Graphical abstract: Image 1